Amyloidosis enhancing activity of bovine amyloid A fibrils in C3H/HeN mice and cynomolgus monkeys (Macaca fascicularis). Issue 3 (12th April 2016) - Tsukawaki, Satomi; Murakami, Tomoaki; Ibi, Kanata; Kuraishi, Takeshi; Hattori, Shosaku; Kai, Chieko; Suzuki, Kazuhiko; Yanai, Tokuma
Abstract: Background: In experimentally induced cases of AA amyloidosis, the development of disease is enhanced by the administration of homogenous or heterogeneous amyloid fibrils. In recent years, cross‐species transmission of animal amyloidosis into human has become of particular concern. Methods: Cynomolgus monkeys ( Macaca fascicularis ) and C3H/HeN mice were inoculated with bovine amyloid fibrils under acute inflammation. Results: Amyloid A deposits were not detected in any of the monkeys, but mild‐to‐severe AA deposits were found in all mice. Conclusions: These results suggest that unlike in rodents, cross‐species transmission of AA amyloidosis is less likely to develop, at least during acute inflammation, in primates.